2018
DOI: 10.1016/j.ultramic.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Image registration of low signal-to-noise cryo-STEM data

Abstract: Combining multiple fast image acquisitions to mitigate scan noise and drift artifacts has proven essential for picometer precision, quantitative analysis of atomic resolution scanning transmission electron microscopy (STEM) data. For very low signal-to-noise ratio (SNR) image stacks - frequently required for undistorted imaging at liquid nitrogen temperatures - image registration is particularly delicate, and standard approaches may either fail, or produce subtly specious reconstructed lattice images. We prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 51 publications
0
67
0
Order By: Relevance
“…Drift is, for instance, very difficult to fully eliminate in cryo-STEM, as the sample holder is cooled to liquid nitrogen temperatures and thus experiences much larger thermal gradients. 20 Instability-induced image deformations can strongly deteriorate the imaging capabilities of modern STEM microscopes which can reach sub-Ångstrom resolution and sub-picometer precision. Distortions are even more pronounced in hyperspectral imaging compared to HAADF imaging due to the longer dwell times.…”
Section: A Tracking and Correcting For Sample Instabilities In Stem mentioning
confidence: 99%
“…Drift is, for instance, very difficult to fully eliminate in cryo-STEM, as the sample holder is cooled to liquid nitrogen temperatures and thus experiences much larger thermal gradients. 20 Instability-induced image deformations can strongly deteriorate the imaging capabilities of modern STEM microscopes which can reach sub-Ångstrom resolution and sub-picometer precision. Distortions are even more pronounced in hyperspectral imaging compared to HAADF imaging due to the longer dwell times.…”
Section: A Tracking and Correcting For Sample Instabilities In Stem mentioning
confidence: 99%
“…It also serves as a base for several other packages, such as pyXem for analyzing SPED data (Johnstone et al, 2019), Atomap for processing atomic resolution STEM data (Nord et al, 2017), and pixStem for working with data from fast pixelated STEM detectors (pixStem devs, 2015). Several other packages exist, like rigidRegistration for doing rigid image registration of atomic resolution image stacks (Savitzky et al, 2018), and wrappers for doing STEM simulations, like PyPrismatic (Ophus, 2017). Other packages for processing data from fast pixelated STEM detectors include py4DSTEM (Savitzky et al, 2019), LiberTEM (Clausen et al, 2019), pycroscopy (Somnath et al, 2019), and fpd (fpd devs, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several images were collected, registered by cross-correlation, and averaged to minimize noise ( Fig. 1D) [3]. A careful evaluation of crystallites using medium angle annular dark field (MAADF) imaging revealed that crystallites are clearly separated by thin regions containing lower atomic number (Z) contrast ( Fig.…”
mentioning
confidence: 99%